Larga lucha de las tradiciones culturales y la globalizacion - Robles Mendoza, Roman (2005)
Modemities in their different forms and of diverse times, have jined inevitable conflicts against natives traditions of the peoples:the firsts by imposing its hegemony and the seconds to maintain itscultural practiices origanal that they are at the same time the soul of his identities. the neomodernity of today, that names globalization, is probañy most influential for the entire world, not only by the presence of the goods that we must consume and use, but by the ecumenical force of the mass media of commnication of satelite technology that by means of some regional samples taken from Ancash and Andahuaylas it explaints the tenacions confrontation of the cultural traditions-to survive and the powerful ompact of the globalization of these times